The right attitude to rain - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Isabel Dalhousie series., 2006)
When friends from Dallas arrive in Edinburgh and introduce Isabel to Tom Bruce, a bigwig at home in Texas, several confounding situations unfurl at once. Tom's young fiancée's roving eye leads Isabel to believe that money may be the root of her love for Tom. But what, Isabel wonders, is the root of the interest Tom begins to show for Isabel herself? And she can't forget about her niece, Cat, who's busy falling for a man whom Isabel suspects of being an incorrigible mama's boy. Of course Grace and Isabel's friend Jamie counsel Isabel to stay out of all of it, but there are irresistible philosophical issues at stake, when to tell the truth and when to keep one's mouth shut.